Levels of C-terminal propeptide of type I procollagen and oxyproline in patients with systemic lupus erythematosus: The relationship between the course of the disease and the structural and functional state of bone tissue - S V. Shevchuk; L. P. Denyschych; L. I. Marynych (Regulatory Mechanisms in Biosystems, 2017)
The high prevalence of osteoporosis in patients with systemic lupus erythematosus (SLE) makes it necessary to study the abnormalities in bone metabolism, its relationship with reduced bone mineral density (BMD) and the impact of the disease on it. The aim of this study was to determine serum levels of C-terminal propeptide of type I procollagen (PICP) and oxyproline in patients with SLE, their comparison with the structural and functional state of the patients’ bone tissue and the course of the disease. We examined 58 female SLE patients. The mean age of the patients was 45.1 ± 1.0 years. The control group included 29 healthy individuals,corresponding in age and sex with the researched group. For every patient, data were recorded on age, body mass index (BMI), menstrual history, smoking, chronic SLE damage (SLICC/ACR DI) and disease activity score (SLEDAI), cumulative glucocorticoid dose, serum concentrations of interleukin-6 (IL-6) and C-reactive protein (CRP), bone formation marker (C-terminal propeptide of type I procollagen) and bone resorption marker (oxyproline). In all patients BMD was measured by DXA (Dual-energy X-ray absorptiometry) at two sites. To determine vertebral compression fractures, female SLE patients were examined with an x-ray of the thoracic and lumbar spine. We established that bone turnover markers showed a significant difference between the SLE patients and the control group, with lower levels of PICP and higher levels of oxyproline in the SLE patients. Alterations of bone metabolism were associated with the severity of the disease, active inflammation (high levels of CRP and IL-6), the age of the patients, and the high cumulative glucocorticoid dose but no correlation was found with disease duration, BMI and smoking. Patients with osteopenia, osteoporosis and fractures were significantly more frequently found among patients with reduced bone formation and increased bone resorption rate. Thus, our findings showed that female SLE patients have alterations of bone metabolism in the form of increasing serum oxyproline and reducing serum C-terminal propeptide of type I procollagen, the correction of which would slow the progression of adverse structural and functional changes in the bone tissue.